MEMBANGUN LEMBAGA PENDIDIKAN UNGGUL YAYASAN INI MEDIA KITA - Anah Furyanah; Ibnu Sina; Haidilia Maharani; Ivan Putranto; Hestu Nugroho Warsto; Ali Maddinsyah (LPPM Universitas Pamulang, 2020)
This community service is titled “Establishing Excellent Education Insitituion”. The purpose of this community service, that was carried out at Ini Media Kita Foundation, in Gunung Sindur, Bogor aims to find out how to establish an excellent education institution. The methods used are survey method, lectures, social services, simulations and also discussions with all teachers and educators at this foundation. The conclusion of this community service was by giving motivation to all teachers and educators in order to unite them in establishing excellent education institution by generating successful students who excel and mastering in science, technology and also religiously. The teachers and educators are given knowledge how to establish an excellent education institution with various kinds of school development.Kata Kunci: Pengembangan sekolah, Lembaga Pendidikan Unggul